CASE REPORT OF RECURRENT RETROPERITONEAL LIPOSARCOMA - Lộc, Vũ; Hữu Đức, Hồ; Anh Bắc, Hoàng (Journal of Health and Aging, 2025)
Retroperitoneal liposarcoma is a rare condition, accounting for approximately 15% of adult soft tissue tumors and has a high recurrence rate. We report a case of recurrent retroperitoneal tumor to evaluate and review treatment approaches. We report a case of a 45-year-old female with a history of surgical resection of a large pelvic retroperitoneal liposarcoma (23x12cm) in 2020, which was well-differentiated (Grade I) but had tumor cells in an ovarian cyst (Stage IIIB). After 3 years of follow-up, the patient was found to have a tumor recurrence at the lower pole of the right kidney measuring 37x38mm on CT scan. The patient underwent complete surgical resection of the recurrent tumor with negative margins (R0), and pathology confirmed well-differentiated liposarcoma (Grade I). After 9 months of followup, no recurrence has been detected. This case emphasizes the importance of regular postoperative follow-up, which helps detect early recurrence when tumors are still small, increases the possibility of complete treatment, and improves patient prognosis.